IJCM_421A : The Lazy-Eye-Scope: A Low-Cost Screening Tool for Early Detection of Amblyopia in Toddlers - Saxena Tanmay; Quazi Anam; Hazarika Partha Protim; Reshmi Bhageerathy; Singhal Deepika; Quazi Zaheer (Wolters Kluwer Medknow Publications, 2024)
Background: Amblyopia is the leading cause of monocular visual acuity impairment that often arises in early childhood with every 2 to 10 children in 100 being affected. Prevention of amblyopia is most effective during early childhood, as interventions become increasingly challenging once the condition progresses and the individual matures. The Lazy-Eye-Scope aims to prevent ocular morbidity in toddlers by early detection of amblyopia. Objective: To develop the The Lazy-Eye-Scope a low cost, technology enabled screening tool that aims to provide easy and affordable amblyopia detection. Methodology: An equipment will be developed to convert normal light into polarized light. It will include a plastic body containing polarising filters and a light source. This light source is directed on the eye through the refracting lens. This introduces a portable device that is extremely scalable, which will be designed for community level use. Conclusion: Thi s device is expect4ed to provide useful insight for the differently abled population including down syndrome and autism. This innovative screening tool holds promise in mitigating ocular morbidity and improving visual outcomes for toddlers worldwide. The simple methodology and usage of the device enables easy use by everyone even if they are not technically skilled.